Stem cell therapy in a child with Duchene Muscular Dystrophy (DMD) at Bangladesh Shishu Hospital and Institute, Dhaka - Kanta, Shayla Imam; Shakil, Khalid Mahmud; Ara, Umme Nusrat; Mahmud, Apel; Shabnam, Nuzhat; Khan, Md Abbas Uddin; Yasmeen, B H Nazma (Northern International Medical College Journal, 2025)
Abstract not available Northern International Medical College Journal Vol. 16 No. 1-2 July 2024-January 2025, Page 753-756